Joint Learning of Sparse Gaussian Processes and Gaussian Process Latent Variable Models for Semi-supervised Tasks - Peres, Ana Alice Ximenes Mota; Mattos, César Lincoln Cavalcante (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e Computacional, 2025)
The speed and variety of collected data have increased in a surprising way, corroborating with the creation of large and diverse datasets. When using such data for training supervised machine learning models, it is necessary to annotate the available samples. However, labeling instances can be challenging, expensive, and time-consuming. In this context, semi-supervised learning models have been extensively researched over the past decades. Among the supervised learning methods, models based on Gaussian Processes (GPs) offer the advantage of quantifying uncertainties and providing significant modeling flexibility. Nevertheless, like several learning strategies, they cannot be directly applied to semi-supervised scenarios. To overcome this issue, the current work proposes a GP-based approach to perform semi-supervised learning. The proposal consists in simultaneously training an unsupervised GP latent variable model (GPLVM) and a supervised sparse GP model. The approach leverages both labeled and unlabeled data to create a more effective final classifier. Additionally, a neural network is included to reproduce the latent variables learned by the GPLVM, which enables scaling and eases its use with unseen data. The introduced solution is evaluated on public datasets and compared with standard semi-supervised approaches from the literature, in both inductive and transductive settings. The experiments indicate that the proposed technique, despite some mixing results, is competitive, especially in transductive learning problems.